Aptitud energético-ambiental de sectores urbanos: conocer la potencialidad de la ciudad para disminuir su impacto sobre el medio ambiente - Viegas, Graciela Melisa (2012)
Urban planning is a tool that allows authorities to conduct a long-term vision for their municipalities, as it influences the future development of cities. Also it plays a key role in creating communities aimed at sustainability. In this regard, it should increase the use of prediction tools and evaluation of sustainability, in urban and built level. City is composed of areas that have different land use, land occupation and coverage of energy services (urban consolidation). Within these, representative sectors called urban mosaics are studied to estimate the fitness of areas for the application of alternative energy systems and implementation of energy efficient use strategies. The MU, understood as a unit composed by different fractions that are its buildings, constitute an analyzable pattern, for application of tools mentioned above. This paper aims to present a tool and procedures for gathering and quantifying urban mosaics, which establish the degree of energetic and environmental aptitude of urban areas to make more efficient use of energy and reduce its unsustainability. The tools are based on objects detection (group of buildings) using techniques of image segmentation on satellite and aerial urban images, on two urban areas. It focuses on the following variables: i. Horizontal dissipation area ii. Constructive system of dissipation horizontal area; iii. Vertical dissipation perimeter; iv. Height of built-up area. Related to energy and environmental fitness, it was observed that the medium consolidation urban mosaic has lower heat losses, makes greater use of buildable area, has less perimeter of vertical envelope, has high quality of envelope, and similar and reduced solar obstruction, respect of low consolidation urban mosaic. The methodology allowed reducing time required and evaluating the energy potential of areas.